2003
DOI: 10.1381/096089203764467144
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Bariatric Surgery on the Veterans Administration Healthcare System: A Cost Analysis

Abstract: Operative treatment of clinically severe obesity reduces obesity-related expenditures and utilization of healthcare resources. The cost of undertaking RYGBP at the VA is offset by reduction of health-care costs within the first year after surgery. These data support allocation of resources to support existing bariatric surgery programs throughout the VA system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 10 publications
0
50
0
1
Order By: Relevance
“…In the United States, the estimate is that 7% of all health costs involve the treatment of obesity and its associated diseases 4 . Similarly, the cost of bariatric surgery is also elevated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the United States, the estimate is that 7% of all health costs involve the treatment of obesity and its associated diseases 4 . Similarly, the cost of bariatric surgery is also elevated.…”
Section: Discussionmentioning
confidence: 99%
“…Paradoxically, Angus et al 10 demonstrated that the hospital costs of bariatric surgery were higher (US$ 11,773.00) in the public health system (Medicare and Medicaid) compared to private care (US$ 4,435.00). Several other authors have reported widely varying costs ranging from US$ 7,800.00 to US$20,500.00 4,[11][12][13][14] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…National studies have revealed substantial regional and socioeconomic status-based variation in the use of WLS (36,37). Patients whose health insurance is based on public financing receive these therapies far less frequently than those covered by private health plans (30), yet the former individuals may be among those who are most in need of surgical intervention (2,38).…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that the cost of surgical interventions for class II to class III obesity is offset by the subsequent reduction in pharmaceutical and hospitalization cost within the first two years after bariatric surgery. 28,29 Additionally, surgical treatment of obesity improves quality-of-life measures. The SOS study found a positive correlation between improvement in quality of life and the degree of weight loss.…”
Section: Overview Of Emerging Concepts In Metabolic Surgerymentioning
confidence: 99%